2018
DOI: 10.2166/wst.2018.402
|View full text |Cite
|
Sign up to set email alerts
|

Long-term investigation of phosphorus removal by iron electrocoagulation in small-scale wastewater treatment plants

Abstract: Small-scale wastewater treatment plants (SWTPs), called Johkasou, are widely used as decentralized and individual wastewater treatment systems in sparsely populated areas in Japan. Even in SWTPs, nutrients should be removed to control eutrophication. An iron electrolysis method is effective to remove phosphorus chemically in SWTPs. However, it is necessary to determine the precise conditions under which phosphorus can be effectively and stably removed in full scale SWTPs for a long period. Therefore, long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…25 Ying et al 26 found that magnetite particles could form in NaCl solution regardless of the presence of Mg 2+ and Ca 2+ ions by electrocoagulation with carbon steel electrodes. Although some studies reported that the electrocoagulation process was efficient for in situ treatment of excess P in wastewater, [27][28][29] complexed wastewater components would lead to electrode passivation and energy increase. 30 Besides, wastewater of low electricity conductivity would lead to high energy consumption in the electrocoagulation process due to the high ohmic drop.…”
Section: Introductionmentioning
confidence: 99%
“…25 Ying et al 26 found that magnetite particles could form in NaCl solution regardless of the presence of Mg 2+ and Ca 2+ ions by electrocoagulation with carbon steel electrodes. Although some studies reported that the electrocoagulation process was efficient for in situ treatment of excess P in wastewater, [27][28][29] complexed wastewater components would lead to electrode passivation and energy increase. 30 Besides, wastewater of low electricity conductivity would lead to high energy consumption in the electrocoagulation process due to the high ohmic drop.…”
Section: Introductionmentioning
confidence: 99%